Women's Gender Identity Negotiation in Social Penetration: A Study of Nusantara Module Participants - Hakim, Wildan; Shambodo, Yoedo; Wibowo, Ganjar; Hanafasyah, Maharani (Al Huwiyah: Journal of Woman and Children Studies, 2025)
This study analyzes the role of women in group dynamics among participants of the Nusantara Module in the Indonesian Student Exchange Program (PMM), using Social Penetration Theory. The focus is on women’s self-disclosure strategies in cross-cultural groups and the influence of gender norms on communication patterns. The research employed a descriptive qualitative method through participant observation, in-depth interviews, and documentation. Findings reveal that women tend to be more selective and cautious in self-disclosure, influenced by privacy, cultural norms, and social safety. However, they also serve as cohesion agents, maintaining group harmony, managing conflicts, and strengthening social ties. This study highlights gender as a crucial variable in understanding social penetration and its implications for inclusive student exchange program design.